Respuestas
Respuesta dada por:
1
Resolución:
Multiplicamos por 6 a todo:
![4 x^{2} + 3x - 12=0
4 x^{2} + 3x - 12=0](https://tex.z-dn.net/?f=4+x%5E%7B2%7D+%2B+3x+-+12%3D0%0A%0A)
Por Formula general: (Anexo Imagen)
x1
![x1= \frac{-(3) + \sqrt{ 3^{2}-4 .(4).(-12) } }{2.(4)}
x1= \frac{-(3) + \sqrt{ 3^{2}-4 .(4).(-12) } }{2.(4)}](https://tex.z-dn.net/?f=x1%3D++%5Cfrac%7B-%283%29+%2B+%5Csqrt%7B+3%5E%7B2%7D-4+.%284%29.%28-12%29+%7D+%7D%7B2.%284%29%7D+%0A%0A%0A)
![x1 = \frac{-3 + \sqrt{9+192} }{8} x1 = \frac{-3 + \sqrt{9+192} }{8}](https://tex.z-dn.net/?f=x1+%3D++%5Cfrac%7B-3+%2B+%5Csqrt%7B9%2B192%7D+%7D%7B8%7D+)
![x1= \frac{-3+ \sqrt{201} }{8} x1= \frac{-3+ \sqrt{201} }{8}](https://tex.z-dn.net/?f=x1%3D++%5Cfrac%7B-3%2B+%5Csqrt%7B201%7D+%7D%7B8%7D+)
![x1= 1,397 x1= 1,397](https://tex.z-dn.net/?f=x1%3D+1%2C397)
x2
![x2= \frac{-(3) - \sqrt{ 3^{2}-4 .(4).(-12) } }{2.(4)}
x2= \frac{-(3) - \sqrt{ 3^{2}-4 .(4).(-12) } }{2.(4)}](https://tex.z-dn.net/?f=x2%3D+%5Cfrac%7B-%283%29+-+%5Csqrt%7B+3%5E%7B2%7D-4+.%284%29.%28-12%29+%7D+%7D%7B2.%284%29%7D+%0A)
![x1 = \frac{-3 - \sqrt{9+192} }{8} x1 = \frac{-3 - \sqrt{9+192} }{8}](https://tex.z-dn.net/?f=x1+%3D+%5Cfrac%7B-3+-+%5Csqrt%7B9%2B192%7D+%7D%7B8%7D)
![x1= \frac{-3- \sqrt{201} }{8} x1= \frac{-3- \sqrt{201} }{8}](https://tex.z-dn.net/?f=x1%3D+%5Cfrac%7B-3-+%5Csqrt%7B201%7D+%7D%7B8%7D)
![x2=-2,147 x2=-2,147](https://tex.z-dn.net/?f=x2%3D-2%2C147)
Multiplicamos por 6 a todo:
Por Formula general: (Anexo Imagen)
x1
x2
Adjuntos:
![](https://es-static.z-dn.net/files/de0/ba7ec6959f79c07cdddf59e962505533.png)
Preguntas similares
hace 6 años
hace 6 años
hace 6 años
hace 9 años
hace 9 años